Pengaruh Motivasi, Disiplin, Pengawasan dan Kondisi Kerja Terhadap Produktivitas Kerja Pegawai Bidang Sumber Daya Air Dinas Pekerjaan Umum Provinsi Bengkulu - Janusi Waliamin; Puspa Ratih; Bedi Agus Yanto; Muhammad Ajid; M. Aliqui Tamarilo (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2022)
This study aims to determine the magnitude of the influence of motivation, discipline, supervision and working conditions on the performance of employees of the Water Resources Department of the Bengkulu Provincial Public Works, using the Multiple Correlation, Determination, Multiple Linear Regression research methods. From the results of the study as a whole there is an effect of motivation, discipline, supervision and working conditions together on the performance of employees in the Water Resources Sector of the Bengkulu Province Public Works Service. Simultaneously it is known that work motivation and work discipline have a significant effect on employee productivity.